The Emergence of Neo-Moderism: A Progressive... = Gagasan Islam Liberal di Indonesia : Pemikiran Neo-Modernisme Nurcholish Madjid, Djohan Effendi, Ahmad Wahib, Abdurrahman Wachid - Greg Barton (Paramadina& Pustaka Antora, 1999)
xxiv, 546 hal.; 21 cm.